The Population Prevalence, Thyroid Cancer and Mortality Risk for Turner Syndrome in South Korea Based on National Health Insurance Service (NHIS) Data - Kim, Sungeun (J Endocr Soc, 2021)
Background: In the present study, we estimated the population prevalence, cancer and mortality risk for Turner syndrome (TS) using data from National Health Insurance Service (NHIS) and Rare Diseases Registry (RDR). Methods: We collected data on subjects with TS who were registered in the RDR between 2012 and 2017. To estimate cancer and mortality risk of TS, the data of TS subjects were compared with and 1:5 age and sex matched controls. Results: In 2017, 2054 individuals with TS were identified out of the total population of 26,249,201 South Korean females and the prevalence was 7.83 per 100,000 persons. In 2017, the distributions of TS prevalence across 10 year old age groups showed 11.44 per 100,000 persons in the group under the age of 10 years, 22.43 per 100,000 persons in teenagers, 18.40 per 100,000 persons in twentieth, 10.24 per 100,000 persons in thirtieth, 4.05 per 100,000 persons in fortieth and 0.39 per 100,000 persons after fiftieth. During 5.3 years, the cancer risk in patients with TS was higher than that of age matched controls [hazard ratio (HR) = 1.813, 95% CI 1.009-3.257]. When cancer is categorized by each organs, thyroid cancer risk in patients with TS was significantly higher than that of age matched controls [hazard ratio (HR) =2.697, 95% CI 1.025-7.097]. The all cause of mortality risk of TS was higher than that of age matched controls [hazard ratio (HR) =3.421, 95% CI 1.623-7.212]. Conclusions: In South Korea, the TS population prevalence was 7.83 per 100,000 persons in 2017. The subjects with TS have higher thyroid cancer and mortality risk than healthy controls. Key words: Prevalence, Turner syndrome, thyroid cancer risk, mortality risk.